Intracerebral haemorrhage: current approaches to acute management. Issue 10154 (6th October 2018) - Cordonnier, Charlotte; Demchuk, Andrew; Ziai, Wendy; Anderson, Craig S
Summary: Acute spontaneous intracerebral haemorrhage is a life-threatening illness of global importance, with a poor prognosis and few proven treatments. As a heterogeneous disease, certain clinical and imaging features help identify the cause, prognosis, and how to manage the disease. Survival and recovery from intracerebral haemorrhage are related to the site, mass effect, and intracranial pressure from the underlying haematoma, and by subsequent cerebral oedema from perihaematomal neurotoxicity or inflammation and complications from prolonged neurological dysfunction. A moderate level of evidence supports there being beneficial effects of active management goals with avoidance of early palliative care orders, well-coordinated specialist stroke unit care, targeted neurointensive and surgical interventions, early control of elevated blood pressure, and rapid reversal of abnormal coagulation.